2011
DOI: 10.1111/j.1471-0307.2011.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breed and other factors on the composition and freezing point of cow’s milk in Poland

Abstract: The milk obtained from six cow breeds (Polish Holstein‐Friesian Black‐White and Red‐White, Simmental, Jersey, Polish Red and Polish Black‐White) managed in the Lubelskie region and the Bieszczady Mountains was analysed. A total of 3618 milk samples collected between 2005 and 2008 were evaluated for the total solids content, percentage concentrations of fat, protein and lactose, and the freezing point: the mean milk freezing point was −0.538°C. The freezing point of milk was influenced by breed, successive lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 7 publications
9
18
0
5
Order By: Relevance
“…The freezing points of milk produced in industrial and traditional systems determined at present study showed no significant differences, being -0.579 and -0.576 ºC respectively (p>0.05) but the highest and the lowest values occurred in winter and summer respectively (p<0.01, table 1). Freezing point is determined by proportion of components which by itself is affected by some factors such as breed, stage of lactation, consumed water, climatic conditions, seasonal effects, heat stress etc [10,12,13]. Freezing point is applied to recognize the milk quality that might be deliberately diluted with water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The freezing points of milk produced in industrial and traditional systems determined at present study showed no significant differences, being -0.579 and -0.576 ºC respectively (p>0.05) but the highest and the lowest values occurred in winter and summer respectively (p<0.01, table 1). Freezing point is determined by proportion of components which by itself is affected by some factors such as breed, stage of lactation, consumed water, climatic conditions, seasonal effects, heat stress etc [10,12,13]. Freezing point is applied to recognize the milk quality that might be deliberately diluted with water.…”
Section: Discussionmentioning
confidence: 99%
“…Freezing point is also an important qualifying specification because it is used to determine the probable addition of water to milk that increases melting point [11]. It is affected by many factors such as breed, milking stage, consumed water, climatic condition, season effects, heat stress etc [10,12,13]. The microbial load is a very important criterion to evaluate the quality status of milk that is an indication of freshness, mainly affected by ambient temperature and the primitive microbial load.…”
Section: Introductionmentioning
confidence: 99%
“…pelo rearranjo de Lobry de Bruyn-Alberda van Ekenstein [12] , ou pela isomerização alcalina [5,21] .…”
Section: Planejamento Fatorialunclassified
“…Em leite pasteurizado, a concentração de lactulose é de cerca de 0,3 g L -1 [5,10,23] , observada no cromatograma da amostra, no tempo de reten- …”
Section: Planejamento Fatorialunclassified
See 1 more Smart Citation